Esophageal low-grade intraepithelial neoplasia overlying multiple leiomyomas: A case report and review of the literature - Pan, Wen; Wu, Junchao; Liu, Chao; He, Yanjun; Yang, Jinlin (Frontiers in Oncology, 2022)
Background Esophageal leiomyoma is the most common benign submucosal mesenchymal tumor. Esophageal intraepithelial neoplasia includes low-grade and high-grade intraepithelial neoplasia. The coexistence of epithelial lesions and the subepithelial lesion is rare. We recorded a case of esophageal low-grade intraepithelial neoplasia (LGIN) overlying multiple esophageal leiomyomas and followed with a review of the literature. Case presentation A 49-year-old female patient came for the treatment of esophageal lesions. The submucosal eminences were observed in the right posterior wall and the left anterior wall of the esophagus by Esophagogastroduodenoscopy (EGD). Additionally, we noticed the mucosa of the right wall with brown background color and the dilated, tortuous vessels by narrow-band imaging (NBI). Then we ensured that the submucosal lesions originated from the esophageal mucosal muscle by endoscopic ultrasonography (EUS) and enhanced CT. Subsequently, the submucosal eminence of the right posterior wall and the overlying mucosal lesion were removed together by endoscopic submucosal dissection (ESD). Postoperative pathological diagnosed esophageal submucosal leiomyoma with focal LGIN. Review EGD showed white scars on the right wall of the upper esophagus three months later, while pathological biopsy showed slight squamous epithelial hyperplasia in the left wall. We decided that the left submucosal lesion can be resected at a selective-time operation, and we continue to follow up as planned. Conclusions The case of intraepithelial neoplasia overlying the submucosal tumor is rare. Either missed diagnosis or overdiagnosis should be avoided through EGD and pathological biopsy.